Sosialisasi Anti Diskriminasi dan Labelling Pada Warga Binaan Pemasyarakatan di Lembaga Pemasyarakatan Perempuan Kelas IIB Jambi - Angraini, Yulita; Vyolicha, Pani; Muhammad, Ali; Biafri, Vivi Silvyani (Indonesian Journal of Community Services, 2023)
Discrimination and labeling are actions that are negative toward individuals. This action is in the form of an insult that has an impact on a person's mentality, especially for correctional inmates. This socialization was carried out at the Jambi Class IIB Women's Penitentiary. This activity was carried out due to the assumption that there was a negative view of the members of the women's correctional facility in Jambi Women's Prison. This socialization was carried out by presenting, explaining, and opening a question-and-answer session regarding discrimination and labeling of prisoners. This activity can increase the understanding of prisoners regarding acts of discrimination and labeling and how to overcome them. It is hoped that the inmates of the correctional facility can be avoided and know how to deal with it acts of discrimination and labeling of inmates in the correctional facility.